ANALISIS KINERJA KARYAWAN DITINJAU DARI MOTIVASI, KOMUNIKASI, DAN KEPUASAN KERJA: ANALISIS KINERJA KARYAWAN DITINJAU DARI MOTIVASI, KOMUNIKASI, DAN KEPUASAN KERJA - Desiyanti, Widya Puspitarani; Wulandari, Jeni; Adistya, Diang (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the effect of motivation, communication, and job satisfaction on employee performance of the transportation and warehousing sector companies in Bandar Lampung. This kind of study uses a quantitative, explanatory methodology. The population in this study were non-managerial employees of the transportation and warehousing sector company in Bandar Lampung, using a sampling technique, namely a saturated sample of 89 respondents. Data obtained by questionnaire using a Likert scale. Methods of data analysis in this study using descriptive analysis and multiple regression analysis. The results of this study indicate that partially and simultaneously motivation, communication, and job satisfaction have a significant effect on employee performance. Intrinsic motivation is the highest rated indicator. Thus, maintaining good intrinsic motivation for employees, can strengthen the sense of maintaining employee performance. The adjusted R square value of 0.584 means that 58.4% means that the independent variables of motivation, communication and job satisfaction affect employee performance while 41.6% are influenced by other variables not researched in this study.